Innovative business models for cleantechs - Carlotta Piantieri (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The energy transition plays a critical role in climate change mitigation, yet it is not occurring at a speed that effectively meets greenhouse gas reduction targets (IPCC, 2018). Policy makers are confronting the challenge to unlock flexibility and efficiency of energy systems. Among others, the European Commission (2016a, 2016b, 2017a, 2017b), the German Ministry of Economics and Energy BMWI (2017) and the former British Department of Energy and Climate Change DECC (2015) call for new business models (BMs) to overcome the inertia prevalent in the system.
Keywords: 330